2020
DOI: 10.3390/cancers12020279
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Estrogens: Turnover Differs between Platinum-Sensitive and -Resistant High-Grade Serous Ovarian Cancer Cells

Abstract: High-grade serous ovarian cancer (HGSOC) is currently treated with cytoreductive surgery and platinum-based chemotherapy. The majority of patients show a primary response; however, many rapidly develop drug resistance. Antiestrogens have been studied as low toxic treatment options for HGSOC, with higher response rates in platinum-sensitive cases. Mechanisms for this difference in response remain unknown. Therefore, the present study investigated the impact of platinum resistance on steroid metabolism in six es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Metabolomics can be used to distinguish between platinum resistance and metabolite levels. Poschner et al used LC-MS to characterize the levels of steroids, active estrogen, and sulfated or aldehyde glucose during the development of platinum resistance in ovarian cancer and found that these metabolites are highly expressed in carboplatin-sensitive cells (Poschner et al, 2020). In a study of non-small cell lung cancer (NSCLC), cisplatin-resistant cells were more sensitive to nutrient deprivation than were sensitive cells, and adding glutamine to cisplatin-resistant cells restored cell death due to nutrient deprivation by increasing the intracellular nucleotide concentration.…”
Section: Application Of Metabolomics In the Evaluation Of Drug Resistance In Cancermentioning
confidence: 99%
“…Metabolomics can be used to distinguish between platinum resistance and metabolite levels. Poschner et al used LC-MS to characterize the levels of steroids, active estrogen, and sulfated or aldehyde glucose during the development of platinum resistance in ovarian cancer and found that these metabolites are highly expressed in carboplatin-sensitive cells (Poschner et al, 2020). In a study of non-small cell lung cancer (NSCLC), cisplatin-resistant cells were more sensitive to nutrient deprivation than were sensitive cells, and adding glutamine to cisplatin-resistant cells restored cell death due to nutrient deprivation by increasing the intracellular nucleotide concentration.…”
Section: Application Of Metabolomics In the Evaluation Of Drug Resistance In Cancermentioning
confidence: 99%
“…We examined the expression (Cq < 35) of 50 genes: 13 uptake and five efflux transporters of steroid precursors, 16 biosynthetic, and 13 metabolic enzymes for estrogens, two nuclear receptors, and all three variants of the membrane estrogen receptor ( Figure 1 ). We used the normal ovarian epithelial cell line HIO-80 and three different chemoresistant HGSOC cell lines: the least chemoresistant OVSAHO (cisplatin IC50~3.7 µM [ 25 ], carboplatin IC50 = 9.4 µM [ 37 ]), moderately chemoresistant Kuramochi (cisplatin IC50~10.4 µM [ 25 ], carboplatin IC50 = 12 µM [ 37 ]), and highly chemoresistant COV362 cell line (cisplatin IC50 = 13.57 µM [ 25 ], carboplatin IC50 = 318.2 µM [ 38 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Estrogens most likely play a more important role in OVSAHO cells because these cells are responsive to estradiol when grown as 3D spheroids, whereas COV362 cells are not [ 39 ]. Additionally, OVSAHO cells are the least chemoresistant of the evaluated cells, and studies have shown that carboplatin-sensitive cells produce more steroid hormones and metabolites than platinum-resistant cells [ 37 ]. Nevertheless, the lack of E1-S metabolism cannot exclude the possibility of the paracrine or endocrine roles of estrogens in the COV362 cells, considering that ESR1 expression at the mRNA level is relatively high, and ERα expression at the protein level is moderate (compared to the OVSAHO and Kuramochi cells) [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The metabolic patterns of cancer cells change after the development of drug resistance. The same drug can induce different metabolic changes in sensitive and drug-resistant cells (47). Thus, metabolomics can be used to detect metabolic changes in cells and their response to drugs to determine whether tumor cells are resistant to drugs, and to monitor drug resistance at an early stage.…”
Section: Metabolomics In Oncology Drugs For Cancer Therapymentioning
confidence: 99%